A Heat Transfer Model of Ammonia Horizontal Falling-film Absorption - Zhang Qiang; Yang Yongping (Zhileng xuebao, 2013)
A new heat and mass transfer model was presented on the basis of Navier-Stokes equation. One-dimensional transformation was conducted on the function of liquid film flow in the process of falling-film, and the Grank-Nicholson Method was used to solve falling-film characteristics. The simulation result of theoretical model was validated with the experiment, and its error is within 17%. Heat and mass transfer coefficient formula was fitted based on the experimental data, and the biggest flow volume of liquid film was obtained in different diameters.